GAMBARAN PARENTAL SELF EFFICACY PADA PEKERJA WISATA DENGAN ANAK USIA SEKOLAH YANG MENGIKUTI PEMBELAJARAN DARING - Putu Gita Kristiana Prasanty; Luh Mira Puspita; Kadek Cahya Utami (Coping: Community of Publishing in Nursing, 2021)
The Covid-19 pandemic has an economic impact due to a decrease in the amount of tourists visiting Bali. The Covid-19 pandemic has also impact in the implementation of online learning. Online learning for school age children still has accompanied by parents. This change in situation has created a challenge for tourism worker parents to raise their children. One factor that influences parenting is parental self-efficacy (PSE). PSE can impact to child development, parental mental health, and parent-child relationship. The aims of this study is to describe parental self-efficacy among tourism workers with school age children who follow online learning. The design of this research was descriptive quantitave with cross-sectional approach. The sample amounted of 154 tourism worker parents with school age children in SD Negeri 1 Beraban, SD Negeri 3 Beraban, and SD Negeri 4 Beraban who were selected by using purposive sampling. The results of this study showed that the school age children of tourism worker parents had an average age of nine years old, majority male sex, and in 2th, 3th, and 4th grade. Tourism worker parents in this study had an average age of 39 years old, majority male sex, last education SMA, have income <Rp. 2.600.000, and have two children. The mean value of PSE was 100,48 with standard deviation of 9,253. The lowest PSE score was 77 and the highest score was 127. The tourism worker parents majority had a low PSE which was 53,9%. Future research are expected to analyze factors related to PSE, provide interventions to improve PSE, and conduct qualitative research to depth-exploration about PSE.